Technical Summary: International expert workshop on systems science for agri-food systems transformation - Brandon, Matthew; Wery, Jacques; Lopez Ridaura, Santiago; Bekunda, Mateete A.; Ortiz, Oscar; Ndibalema, Gloriana (International Institute of Tropical Agriculture, 2024)
During a three-day workshop held in May 2024, over forty CGIAR researchers gathered to discuss the current status of systems science across CGIAR, together with representatives from partner institutions.